Developmental arsenic exposure is associated with sex differences in the epigenetic regulation of stress genes in the adult mouse frontal cortex - Solomon, Elizabeth R. (Toxicol Appl Pharmacol, 2020)
Previously, we reported sex-dependent changes to global histone modifications and impairment of executive function in adult mice exposed to moderate levels of arsenic during early development. The present study investigated the effects of developmental arsenic exposure (DAE) on gene specific histone 3 lysine 9 acetylation (H3K9ac) and tri-methylation (H3K9me3) in the frontal cortex of male and female adult C57BL/6J mice. Dams were exposed to 50ppb arsenic in drinking water prior to and throughout gestation, and until pup weaning; once weened, the pups were given tap water (< 5ppb arsenic) and raised to postnatal day 70. Using chromatin immunoprecipitation and qPCR, we assessed changes in H3K9 regulatory markers and mRNA expression levels of the stress signaling genes, Nr3c1, Crh, Crhr1, Hsd11b1, and Fkbp5. In female DAE mice, H3K9ac association with the Crh promoter was increased and this corresponded with increased Crh mRNA expression. Crhr1 mRNA expression was increased in female DAE mice, while expression was reduced in male DAE mice. DAE resulted in chromatin and mRNA changes associated with decreased glucocorticoid signaling in male but not female frontal cortex: increased H3K9ac association with Fkbp5 and a corresponding increase in Fkbp5 mRNA expression. In addition, there was a decrease of Hsd11b1 mRNA expression in DAE males. These results suggest a sex-dependent response to arsenic during embryonic development leading to different patterns of gene regulation and expression.